Multipoint Iterative Methods for Finding All the Simple Zeros in an Interval - T. Lotfi; F. Soleymani; S. Sharifi; S. Shateyi; F. Khaksar Haghani (Journal of Applied Mathematics)
Two new families of multipoint without memory iterative methods with eighth- and sixteenth-orders are constructed using the symbolic software Mathematica. The key idea in constructing such methods is based on producing some generic suitable functions to reduce the functional evaluations and increase the order of convergence along the computational efficiency. Again by applying Mathematica, we design a hybrid algorithm to capture all the simple real solutions of nonlinear equations in an interval. The application of the new schemes in producing fractal pictures is also furnished.